Metropolitan Econometric Electric Utility Forecast Accuracy - Fullerton, Thomas M.; Novela, George; Torres, David; Walke, Adam G. (International Journal of Energy Economics and Policy, 2015)
El Paso Electric Company (EPEC) is the sole commercial electricity provider for two metropolitan economies in the southwestern desert region of the United States: El Paso, Texas and Las Cruces, New Mexico. A publicly traded corporation, EPEC employs a structural econometric system of equations model to forecast energy sales for various customer classes. Although the modeling system has provided reliable inputs to annual corporate planning efforts at EPEC, its historical track record has not previously been formally assessed for forecast accuracy. Both descriptive and inferential statistics are used to evaluate the EPEC model's forecasting performance. Results indicate that accurate prediction of electricity usage in this service area is an elusive target. Those results are similar to what has been documented for other regional economic variables. Keywords: Energy forecasting, Statistical tests, Forecast accuracy evaluation JEL Classifications: Q47; M21; R15